2016
DOI: 10.1210/jc.2015-4026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Intensity on Glucose Requirements to Maintain Euglycemia During Exercise in Type 1 Diabetes

Abstract: Our findings support the predicted inverted-U relationship between exercise intensity and glucose requirement. However, the relationship between iv and oral glucose requirements needs to be investigated to translate these GIR data to clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 40 publications
5
52
1
1
Order By: Relevance
“…However, when plasma insulin is at near basal levels, blood glucose level often remains stable or fall at a low rate in response to exercise of moderate intensity, but not if aerobic exercise is intense since intense aerobic exercise under basal or near basal insulinemic conditions is associated with a rise in blood glucose level . Overall, their appears to be an inverted U‐shape in the relationship between aerobic exercise intensity and muscle glucose disposal, with the highest risk for hypoglycemia likely occurring at about 50% of the individuals’ maximal aerobic capacity …”
Section: The Impact Of Exercise On Blood Glucose Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when plasma insulin is at near basal levels, blood glucose level often remains stable or fall at a low rate in response to exercise of moderate intensity, but not if aerobic exercise is intense since intense aerobic exercise under basal or near basal insulinemic conditions is associated with a rise in blood glucose level . Overall, their appears to be an inverted U‐shape in the relationship between aerobic exercise intensity and muscle glucose disposal, with the highest risk for hypoglycemia likely occurring at about 50% of the individuals’ maximal aerobic capacity …”
Section: The Impact Of Exercise On Blood Glucose Levelsmentioning
confidence: 99%
“…It is more likely to occur with mod intensity exercise compared with intermittent high intensity exercise. Perhaps counterintuitively, hypoglycemia is less likely with high intensity exercise than with moderate intensity effort …”
Section: Hypoglycemiamentioning
confidence: 99%
“…[1], blood glucose generally drops during low- and moderate-intensity exercise in people with type 1 diabetes, but it may even increase during and after high-intensity exercise [7]. Adrenaline and noradrenaline have been shown to be the main regulators to target for avoiding blood glucose decreases during high-intensity exercise due to increased rates of glycogen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Shetty et al . [1] found an inverted U-shaped relationship between exercise intensity and glucose requirement investigated via glucose infusion rate in a euglycemic clamp. In line with valuable reviews [2, 3], it is suggested to adapt therapy to avoid exercise-induced hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…A clamp study found IV glucose demand changed as the level of physical exercise was increased consecutively. The glucose infusion rate was increased at a moderately intense level of exercise, while the need for IV glucose disappeared during high-intensity exercise [92]. The latter illustrates the complexity involved in attempting to take physical activity into account, as the need for insulin can vary during exercise in ways that are difficult to predict.…”
Section: Methodsmentioning
confidence: 99%